Facile Substituent Exchange at H‐Phosphonate Diesters Limiting an Effective Synthesis of D‐Phosphonate Diesters. Issue 8 (30th July 2019) - Lee, Keng Lung; Feld, Joey; Ben‐Tal, Yael; Guo, Zhaoyang; Hume, Paul; Leitao, Erin M.
Abstract: Research on using H ‐phosphonate diesters to introduce phosphorus functionality into molecules and polymers, some of which have medicinal applications, has recently attracted a lot of attention. Deuterium labelling to yield the corresponding D ‐phosphonate diesters, although desirable in order to help with the mechanistic elucidation of reactions containing H ‐phosphonate diesters, has been demonstrated to be a challenge. Deuterium exchange at H ‐phosphonate diesters using D2 O, MeOD and ND2 Bn has shown competitive behavior with hydrolysis, alcoholysis and aminolysis reactions, respectively. This facile substituent exchange for the addition of D2 O and MeOD can be attributed to the similar energy required to eliminate ROH or H2 O (ROD or HOD, R= i Pr, Et, Me) from a pentavalent P(V) intermediate which is generated from axial delivery of an OD or OR group from D2 O and MeOD, respectively. The trend in reaction rate for the exchange processes follows the order of R=Me>Et> i Pr in (RO)2 P(O)H and also depends on the nucleophilicity of the incoming group. Attempted synthesis of D ‐phosphonate diesters directly from PCl3 and alcohols or via lithiation reactions further demonstrated just how sensitive the H/D‐scrambling process is. These results have implications for the general reactivity of H ‐phosphonate diesters towards water, alcohol, and amines and their potential to selectively undergo substitution at either P‐ OR or P‐ H . Moreover, insight into the mechanism(s) of selective deuterium exchange, for example to give D ‐phosphonate diesters via the direct exchange of D for H, was illuminated through this research. Abstract : Label ‐less . H ‐phosphonate diesters are susceptible to a wide range of reactivity in the presence of water, alcohols and amines inhibiting their ability to undergo selective deuterium exchange reactions to allow isolation of D ‐phosphonate diesters.